Monozygotic twins with myocarditis and a novel likely pathogenic desmoplakin gene variant - Antheia Kissopoulou; Eva Fernlund; Christina Holmgren; Eira Isaksson; Jan‐Erik Karlsson; Henrik Green; Jon Jonasson; Rada Ellegård; Hanna Klang Årstrand; Anneli Svensson; Cecilia Gunnarsson (ESC Heart Failure)
Abstract Myocarditis most often affects otherwise healthy athletes and is one of the leading causes of sudden death in children and young adults. Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetically determined heart muscle disorder with increased risk for paroxysmal ventricular arrhythmias and sudden cardiac death. The clinical picture of myocarditis and ARVC may overlap during the early stages of cardiomyopathy, which may lead to misdiagnosis. In the literature, we found several cases that presented with episodes of myocarditis and ended up with a diagnosis of arrhythmogenic cardiomyopathy, mostly of the left predominant type. The aim of this case presentation is to shed light upon a possible link between myocarditis, a desmoplakin (DSP) gene variant, and ARVC by describing a case of male monozygotic twins who presented with symptoms and signs of myocarditis at 17 and 18 years of age, respectively. One of them also had a recurrent episode of myocarditis. The twins and their family were extensively examined including electrocardiograms (ECG), biochemistry, multimodal cardiac imaging, myocardial biopsy, genetic analysis, repeated cardiac magnetic resonance (CMR) and echocardiography over time. Both twins presented with chest pain, ECG with slight ST‐T elevation, and increased troponin T levels. CMR demonstrated an affected left ventricle with comprehensive inflammatory, subepicardial changes consistent with myocarditis. The right ventricle did not appear to have any abnormalities. Genotype analysis revealed a nonsense heterozygous variant in the desmoplakin (DSP) gene [NM_004415.2:c.2521_2522del (p.Gln841Aspfs*9)] that is considered likely pathogenic and presumably ARVC related. There was no previous family history of heart disease. There might be a common pathophysiology of ARVC, associated with desmosomal dysfunction, and myocarditis. In our case, both twins have an affected left ventricle without any right ventricular involvement, and they are carriers of a novel DSP variant that is likely associated with ARVC. The extensive inflammation of the LV that was apparent in the CMR may or may not be the primary event of ARVC. Nevertheless, our data suggest that irrespective of a possible link here to ARVC, genetic testing for arrhythmogenic cardiomyopathy might be advisable for patients with recurrent myocarditis associated with a family history of myocarditis.